1998
DOI: 10.1159/000017324
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting the Existence of an Activity-Dependent Astrocyte-Neuron Lactate Shuttle

Abstract: Mounting evidence from in vitro experiments indicates that lactate is an efficient energy substrate for neurons and that it may significantly contribute to maintain synaptic transmission, particularly during periods of intense activity. Since lactate does not cross the blood-brain barrier easily, blood-borne lactate cannot be a significant source. In vitro studies by several laboratories indicate that astrocytes release large amounts of lactate. In 1994, we proposed a mechanism whereby lactate could be produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
481
0
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(510 citation statements)
references
References 30 publications
(44 reference statements)
21
481
0
8
Order By: Relevance
“…Glucose is converted to glucose-6-phosphate (G6P) via HXK in the first step of glycolysis, where it may be further converted to other bioenergetic intermediates by highly regulated enzymes, such as phosphofructokinase, ultimately yielding pyruvate and ATP (23). Pyruvate may be converted to lactate by lactate dehydrogenase (LDH) and shuttled via monocarboxylate transporters (MCTs) into neurons, providing energy for receptor trafficking, spine formation and other neurotransmission events (24, 25). In schizophrenia, cognitive impairment correlated with decreases in striatal cytochrome oxidase and cortical glucose utilization (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is converted to glucose-6-phosphate (G6P) via HXK in the first step of glycolysis, where it may be further converted to other bioenergetic intermediates by highly regulated enzymes, such as phosphofructokinase, ultimately yielding pyruvate and ATP (23). Pyruvate may be converted to lactate by lactate dehydrogenase (LDH) and shuttled via monocarboxylate transporters (MCTs) into neurons, providing energy for receptor trafficking, spine formation and other neurotransmission events (24, 25). In schizophrenia, cognitive impairment correlated with decreases in striatal cytochrome oxidase and cortical glucose utilization (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…According to this, uptake of released neurotransmitter glutamate into astrocytes leads to increased glycolysis and production of lactate, which is subsequently exported to neurons (Bittar et al, 1996;Pellerin et al, 1998). Indeed, neurons in culture as well as other brain tissue preparations are able to maintain functional activity using lactate, other monocarboxylates, and certain amino acids as energy substrates (Schurr et al, 1988;Hertz et al, 1988;Brown et al, 2001;Waagepetersen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of muscle energy metabolism have established that lactate is almost always produced during intense muscle activity under fully aerobic conditions, and that lactate serves to shuttle energy substrate from one cell or cellular compartment to another (Brooks, 1986;Gladden, 2004). Recent studies have suggested that lactate might serve a similar role in brain energy metabolism (Pellerin et al, 1998;Schurr, 2005). In vivo measures of brain lactate with microsensors in rats (Hu and Wilson, 1997) and with proton magnetic resonance spectroscopy (1H-MRS) in humans (Prichard et al, 1991;Sappey-Marinier et al, 1992;Frahm et al, 1996) have demonstrated brain lactate increases during neuronal activation.…”
Section: Introductionmentioning
confidence: 99%